Changes to the turbulent kinematics of a volcanic plume inferred from lightning data. Issue 10 (27th May 2015) - Behnke, Sonja A.; Bruning, Eric C.
Abstract The 2009 Redoubt Volcano eruption produced a series of explosive events, the largest of which produced episodes of volcanic lightning similar to thunderstorms. Flash energy spectra were calculated from lightning mapping data collected during the eruption. The spectra were compared to the turbulence characteristics expected from each stage of plume development. Small flash length scales present at early times were associated with the gas thrust and initial convective stages. Increases in flash length scales and flash energy as the explosive events progressed were associated with an increase in volume of the plume. Spectra with a large range in flash length scales (0.2–10 km) and a spectral peak at small flash length scales (< 1 km) were associated with a superposition of spectra from gas thrust, convective, and umbrella/ash cloud regions. An approximate 5/3 power law slope was observed on the order of 10 min after gas thrust forcing had ended and the transition to a drifting ash cloud was underway, which may reflect the dissipating state of the drifting ash cloud.